FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING DI KECAMATAN DAWE - Anita Dyah Listyarini; Novan Korneawan Pangestu; Luluk Cahyanti (Poltekkes Kemenkes Aceh, 2023)
Child health problems which are currently a top priority that the government wants to improve are regarding child development. Many developmental problems that occur in children, one of which is stunting. Stunting is a topic that needs attention from all groups considering the impact it causes. Stunting is a topic that needs attention from all groups considering the impact it causes. For children who survive, stunting can lead to increased morbidity, poor cognitive ability, short stature, increased risk of perinatal and neonatal death, decreased productivity as adults, and increased chronic disease. The aim of this study was to determine the factors associated with the incidence of stunting in the Dawe sub-district. The method used is cross sectional design and simple random sampling. The sample in this study were 107 samples. The results of the analysis stated that there was a relationship between knowledge (p value 0.000 < ɑ 0.05) and the mother's employment status (p value 0.003 < ɑ 0.05) with the incidence of stunting in Dawe District and there was no relationship between history of pregnancy and new baby weight. born with a stunting incident in Dawe sub-district. The conclusion is that there is a relationship between knowledge and employment status of the mother and the incidence of stunting in Dawe District and there is no relationship between history of pregnancy and newborn weight and the incidence of stunting in Dawe District.